2011
DOI: 10.4274/tpa.46.03
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’deki 11, 13, 15 yaşındaki okul çocuklarının fiziksel etkinlik düzeylerinin demografik özellikler, beslenme alışkanlıkları ve hareketsiz yaşam davranışlarıyla ilişkisi

Abstract: R Re el la at ti io on ns sh hi ip p b be et tw we ee en n p ph hy ys si ic ca al l a ac ct ti iv vi it ty y l le ev ve el l a an nd d d de em mo og gr ra ap ph hi ic c c ch ha ar ra ac ct te er ri is st ti ic cs s, , e ea at ti in ng g h ha ab bi it ts s a an nd d s se ed de en nt ta ar ry y b be eh ha av vi io or rs s o of f T Tu ur rk ki is sh h s sc ch ho oo ol l c ch hi il ld dr re en n a ag ge ed d 1 11 1, , 1 13 3 a an nd d 1 15 5 y ye ea ar rs s E Et th he em m E Er rg gi in nö öz z, , M Mü üj jg ga an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Similarly, many studies also reported that male adolescents were more active than female ones. [8,20,22,[37][38][39] In another study, it was found that female adolescents were less encouraged to attend to physical activities by their parents. [40] The reason of the significant differences in the physical activity levels between the two sexes may be due to sociocultural features of the individuals, since being physically active is much more accepted for males than females in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many studies also reported that male adolescents were more active than female ones. [8,20,22,[37][38][39] In another study, it was found that female adolescents were less encouraged to attend to physical activities by their parents. [40] The reason of the significant differences in the physical activity levels between the two sexes may be due to sociocultural features of the individuals, since being physically active is much more accepted for males than females in Turkey.…”
Section: Discussionmentioning
confidence: 99%